Impact of SYNTAX Scores on the Long-Term Outcomes of Coronary Artery Bypass Grafting and Percutaneous Coronary Intervention for Left Main Coronary Artery Disease - Murteza, Faiq; Albab, Chabib Fachry; Habibah, Almas Talida; Mas'udi, Achmad Fayyad; Pravitasari, Vemaniarti Lian; Rajanagara, Arya Satya; El-Ma'i, Zaha (Folia Medica Indonesiana, 2023)
The Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) score was designed to predict the post-procedural risk associated with percutaneous coronary intervention (PCI) or surgical revascularization. This study aimed to evaluate the long-term outcomes of PCI and coronary artery bypass grafting (CABG) by comparing several existing studies. A systematic search was performed using the PubMed (MEDLINE) and ScienceDirect databases. This systematic review included studies that examined differences in the outcomes of PCI and CABG for left main coronary artery (LMCA) stenosis. This was a systematic review study in which we reviewed original cross-sectional and cohort studies. The search was conducted from February 1st until February 2nd, 2023. The quality assessment of the studies was carried out using the criteria outlined in the Newcastle-Ottawa Scale (NOS). According to the final assessment, all the original research included had a mean NOS score of 8, indicating excellent quality. The literature search yielded 1,675 studies, five of which were selected for the final analysis. A total of 5,494 patients underwent PCI and CABG. This study found that there were variations in outcomes among patients with low, medium, and high SYNTAX scores for long-term major adverse cardiac or cerebrovascular events (MACCE) and long-term mortality. However, similar outcomes were observed in long-term revascularization, long-term stroke, and long-term myocardial infarction (MI). This study concluded that patients with LMCA stenosis and SYNTAX scores ranging from low to high may have different long-term outcomes. CABG is associated with a lower incidence of mortality, repeat revascularization, MI, and MACCE compared to PCI. On the other hand, an association exists between PCI and a lower incidence of stroke.